EVALUATION OF INTERELEMENT EFFECTS OF Ag – Cu – Ti TERNARY SYSTEM BY X-RAY FLUORESCENCE TECHNIQUE - Juma, Thamir Abdul-Jabbar (Al-Nahrain Journal of Science, 2010)
The interelement effects of Ag-Cu-Ti Ternary system was studied by x-ray fluorescence toobtain the concentration of each element accurately. Ternary compacted of high pure metals of Ag-Cu-Ti as a green pellets were prepared. Wavelength dispersive technique was used to measure thefluorescent intensities of ternary system at the same operation condition. The intensities of theternary elements in the spectrum were non-linearly related to concentration of each element due tothe absorption and enhancement effects. Ag absorbs x-ray fluorescence of Ti more than Cu. Binaryinfluence coefficients were obtained from the values of relative intensities to calculate the elementalconcentration of ternary system using BB (Bettie – Berssey) algorithm